Multi-scale Scattering Transform in Music Similarity Measuring - Wang, Ruobai (My University, 2017)
Scattering transform is a Mel-frequency spectrum based, time-deformation stable method, which can be used in evaluating music similarity. Compared with Dynamic time warping, it has better performance in detecting similar audio signals under local time-frequency deformation. Multi-scale scattering means to combine scattering transforms of different window lengths. This paper argues that, multi-scale scattering transform is a good alternative of dynamic time warping in music similarity measuring. We tested the performance of multi-scale scattering transform against other popular methods, with data designed to represent different conditions.
Thesis (Master's)--University of Washington, 2017-06
Keywords: music similarity; scattering transform; time deformation; Electrical engineering; Electrical engineering